ANALYSIS OF THE PRINCIPLE OF JUSTICE IN THE PROCESS OF RESPONSIBILITY FOR CORRUPTION CRIMES - Puspitasari, Feni; Fikri, KMS Novyar Satriawan; Azhar, Ali (International Journal of Multidisciplinary Research and Literature, 2024)
Corruption in Indonesia is no longer a new legal issue because the problem of corruption has existed for thousands of years, both in developed countries and developing countries, including Indonesia. Today's corruption problem in Indonesia is so severe that it has become an extraordinary problem because it has infected and spread to all levels of society. Corruption crimes in ancient times were regulated in the Criminal Code due to the dynamics that developed in society. The regulation underwent changes where it was special, or lex was then regulated for the first time in Law Number 31 of 1999 jo. Amendment to Law Number 20 of 2001 concerning the Eradication of Corruption Crimes. During its activities, corruption is carried out by the holders of the highest power, who have positions that are mostly the result of election winners in a party. The PTPK Law states that people who commit corruption must compensate the state due to the economic and social impact of a region that it causes on the state's finances. On the way, the addition of prison sentences for heavy corruptors provides a deterrent effect for corruption perpetrators, with which it is hoped that corruption crimes can be reduced